Appraising Microfinance Institutions - World Bank (Washington, DC, 2012)
Appraisals are an integral part of the funding process. Appraisals (also commonly called due diligence) help funders to determine the capacity of microfinance institutions (MFIs) and to make decisions related to capitalizing an MFI or providing support for technical assistance. Information obtained as part of an appraisal process helps funders make decisions on funding levels, funding instruments, and the overall structure of a deal. The guide was updated in 2008 to reflect the latest trends in the industry. It incorporates the latest microfinance knowledge and good practices to form a detailed roadmap that analysts can use to evaluate MFIs. The updated guide includes new sections on savings, poverty outreach, information systems, and risk management. Appraisal guide for MFI promotes an industry standard for appraisals and is available free to funders, consultants, and others undertaking appraisals.